68Ga-DOTA-TATE PET/CT for Molecular Imaging of Somatostatin Receptor Expression in Metastasizing Epithelioid Hemangioendothelioma: Comparison With 18F-FDG. (November 2017) - Derlin, Thorsten; Hueper, Katja; Soudah, Bisharah
Abstract : Abstract: Epithelioid hemangioendothelioma (EHE) is a rare tumor originating from vascular endothelial or pre-endothelial cells. It has the potential to metastasize. We present the case of a 51-year-old woman with metastasizing EHE who underwent both 18 F-FDG and 68 Ga-DOTA-TATE PET/CT for staging of disease and for evaluation of targeted radionuclide therapy potential. On 68 Ga-DOTA-TATE PET scans, intense tracer accumulation was observed in metastases. Besides the increased glucose metabolism in EHE, this case highlights the potential of 68 Ga-DOTA-TATE PET/CT for restaging of EHE and the option of targeted radionuclide therapy in this entity.